Corelation of Stress Levels During Covid-19 Pandemic and Menstrual Cycle of Diploma IV Midwifery Student of Sebelas Maret University - Nareswari, Indi; Azizah, Hudzaifah Alief Fath; Murniasih, Murniasih; Sinaga, Ruth Dearani; Novika, Revi Gama Hatta; Sari, Atriany Nilam (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2021)
The pandemic period caused by the SARS-CoV2 virus is a global problem that has an impact on the community, including students. Task load and online learning systems are factors that cause students to experience stress, this can be one of the causes of disruption of the menstrual cycle. Changes in the menstrual cycle is a health problem for some women. This study aims to link stress levels during the coronavirus disease 19 pandemic to the menstrual cycle of UNS Diploma IV Midwifery students.This study analyzed primary data of observational analytic with a cross sectional design. The independent variable in this study was stress on students, while the dependent variable in this study was changes in the menstrual cycle. We used 84 sample consisting of all midwifery student in Sebelas Maret University with an age range of 17-22 years. There is no relationship between stress during the coronavirus disease 19 pandemic and student menstrual cycles with a p value of 0.925 indicating that there is no significant relationship between the two variables tested (p < 0,05). There is no significant relationship between stress levels during the pandemic and the menstrual cycle of UNS midwifery diploma IV students.